The Dispute Between Thinking Styles and Thinking Skills Among Technical Students - Heong, Yee Mei; Michael, Karen Sharmini; Shuhada, Nurfara; Mohamad, Mimi Mohaffyza; Jiar, Yeo Kee; Fuada, Syifaul (Online Journal for TVET Practitioners, 2023)
Thinking style is one thing that can help students in solving problems by knowing the students’ own style. The style of thinking is not an ability but more towards how to use the existing abilities of each individual. Similarly, thinking skills can help students to solve problems and can make students smart in thinking about things. Thinking skills can be formulated as the process of using the mind to find a solution or understanding of something. Thinking skills also allow students to integrate each newly experienced experience into each individual’s mind box. The aim of this study was to identify the thinking style patterns and the level of thinking skills between the demographic factors among technical students. The design of this study was descriptive and inferential with a quantitative approach. A total of 273 technical students from the Faculty of Technical and Vocational Education (FPTV) at Universiti Tun Hussein Onn Malaysia (UTHM) were randomly selected as a sample covering the fields of Building Construction (BBB), Catering (BBC), Welding and Metal Fabrication (BBD), Electrical and Electronics (BBE), Creative Multimedia (BBF) and Refrigeration and Air Conditioning (BBG). A set of modified questionnaires from past studies were used as research instruments. Majority of technical students have a balanced thinking style and follow a critical and creative thinking style. The majority of all technical students at FPTV has a level of mastery of all three thinking skills analytical, practical and creative. Among the three types of skills, the majority of technical students have a level of mastery of high practical thinking skills, followed by creative thinking skills and analytical thinking skills. It is hoped that this study can provide guidance to students, lecturers and institutions to improve the Way of teaching and learning in accordance with the thinking style and thinking skills of students.